PWE-008 A Novel Sampling Device For Collecting Mucocellular Material From The Rectum. (9th June 2014) - Booth, J; Lacy-Colson, J; Norwood, M; Murray, C
Abstract : Introduction: Earlier detection of colorectal and other gastrointestinal malignancies is an urgent objective. Currently much effort is directed at the development of in vitro diagnostic tests that evaluate informative protein or DNA biomarkers in stool or blood samples. Stool samples are inconvenient to collect, require special handling facilities, and suffer from contamination that may interfere with molecular assays. Blood samples, while more convenient, may not be as informative early in the disease process. Several studies have shown that significant numbers of exfoliated cells and their products are retained in a muco-cellular layer overlying the colonic mucosa but distinct from the stool itself, and that this material flows toward the rectum, where it can be captured for analysis. Methods: Origin Sciences has developed a novel sampling device, which incorporates an inflatable nitrile membrane. Following insertion into the unprepared rectum via a standard proctoscope, the membrane is inflated to make contact with the rectal mucosa for 10 seconds. The membrane is then deflated and retracted into the device prior to removal from the patient. Upon retraction the material sampled from the rectal mucosa is retained on the inverted membrane, which acts as a receptacle for the addition of buffer to preserve the material for subsequent analysis. Results: The sampler has been tested in over 2000 patients and healthy volunteers, and has shown excellent patient acceptability. Tests and in vitro experiments with monolayers of cultured human cells indicate that the membrane captures intact cells, which are easily washed off the membrane for further investigation. Mucous-associated soluble material captured by the device is rich in protein and nucleic acids. Levels of soluble protein present in the buffer varied between 90 and 3000 µg/mL, with a mean of 710 µg/mL. As part of a programme to identify novel cancer biomarkers, Origin Sciences has detected informative auto-antibody isotypes IgA, IgG and IgM by ELISA. The same preparation is also rich in nucleic acids; DNA has been found in amounts ranging from 0.5 to 21.9 ug/mL. This DNA is suitable for amplification and sequencing, since we have been able to detect a number of genes by quantitative PCR. Conclusion: The sampling device represents a novel and minimally invasive means of capturing biomarker-rich material from the unprepared rectum. Since there is minimal contamination by stool, the material collected is readily analysable, in principle lending itself to point-of-care tests for a wide range of indications, including infectious and inflammatory diseases of the GI tract in addition to malignancy. The device can be used as a robust means of collecting material for later analysis by a wide range of technologies. Disclosure of Interest: None Declared.